2022
DOI: 10.1038/s41467-022-30629-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of NAFLD and bariatric surgery on hepatic and adipose tissue mitochondrial biogenesis and respiration

Abstract: Impaired mitochondrial oxidative phosphorylation (OXPHOS) in liver tissue has been hypothesised to contribute to the development of nonalcoholic steatohepatitis in patients with nonalcoholic fatty liver disease (NAFLD). It is unknown whether OXPHOS capacities in human visceral (VAT) and subcutaneous adipose tissue (SAT) associate with NAFLD severity and how hepatic OXPHOS responds to improvement in NAFLD. In biopsies sampled from 62 patients with obesity undergoing bariatric surgery and nine control subjects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 60 publications
2
16
0
Order By: Relevance
“…There is now growing evidence for different adaptive changes of hepatic mitochondrial capacity in NAFL, NASH and fibrosis [14,16,19]. The present study confirms upregulation of TCA-and βoxidation-linked mitochondrial respiration in obese humans with NAFL, but not NASH [14].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…There is now growing evidence for different adaptive changes of hepatic mitochondrial capacity in NAFL, NASH and fibrosis [14,16,19]. The present study confirms upregulation of TCA-and βoxidation-linked mitochondrial respiration in obese humans with NAFL, but not NASH [14].…”
Section: Discussionsupporting
confidence: 79%
“…A recent high-resolution respirometry study found that only a group with definite histopathological NASH exhibited lower fatty acid oxidation, when compared to NAFL or borderline NASH groups [17]. Liver respiration was also nominally highest in NAFL, intermediate in NASH and nonsteatotic obesity and lowest in non-steatotic humans in another study [16]. The present study extends these findings by showing an inverse relationship between mitochondrial capacity and mitochondrial diameter across all obese groups combined, suggesting that mitochondrial elongation reflects low respiratory competence.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Increasing numbers of publications have reported that impaired mitochondrial functions are involved in various diseases, such as diabetes, Parkinson's disease, and nonalcoholic fatty liver disease [ 41 44 ]. Mitochondrial biogenesis is the process by which new mitochondria are formed in tissues and cells, and this process is activated by different signals in response to internal and external environmental stimuli [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing numbers of publications have reported that impaired mitochondrial functions are involved in various diseases, such as diabetes, Parkinson's disease, and nonalcoholic fatty liver disease (41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%